Plasma IgG glycan dynamics predict adverse reactions in allergen immunotherapy - Ran Zhao; Na Dong; Zhikang Yu; Yue Xie; Weilong Zhang; Qin Wang; Lang Yuan; Yongyu Tang; Shifang Ren; Xiaoyan Dong (Clinical Proteomics, 2026)
Abstract Allergen-specific immunotherapy (AIT) is the only disease-modifying treatment for allergic rhinitis and asthma, but objective biomarkers for monitoring immune tolerance and predicting adverse reactions remain lacking. ImmunoglobulinG (IgG) glycosylation has been validated as an effective biomarker in numerous inflammatory diseases. This study aimed to explore plasma IgG N-glycan dynamics as predictive markers for AIT tolerance and adverse events. We enrolled 37 patients with allergic asthma or rhinitis undergoing subcutaneous AIT, 26 patients were longitudinally sampled at three time points: pre-treatment, maintenance initiation, and after more than 6 months of maintenance therapy. IgG N-glycans were analyzed by ultra-performance liquid chromatography (UPLC). Longitudinal analysis showed total IgG galactosylation and sialylation gradually increased, while bisecting glycans decreased during AIT. Among 37 patients, those with adverse reactions exhibited significantly elevated GP6, reduced GP18, GP23, lower galactosylation and sialylation, and increased bisecting glycans at baseline compared with tolerant patients. Receiver operating characteristic (ROC) curve analysis revealed that the combined glycan model achieved an area under the curve (AUC) of 0.863 for adverse reaction prediction. These findings demonstrate that IgG N-glycosylation remodeling correlates with AIT progression and can serve as a potential pretreatment biomarker for risk stratification. Plasma IgG N-glycan profiling provides a minimally invasive, mechanism-based tool to improve AIT safety and efficacy, which deserves further multicenter validation.